Palliative care team visits. Qualitative study through participant observation (Colombia Medica, 2016)
Objectives:To describe the clinical encounters that occur when a palliative care team provides patient care and the features that influence these encounters and indicate whether they are favorable or unfavorable depending on the expectations and feelings of the various participants.Methods:A qualitative case study conducted via participant observation. A total of 12 observations of the meetings of palliative care teams with patients and families in different settings (home, hospital and consultation room) were performed. The visits were follow-up or first visits, either scheduled or on demand. Content analysis of the observation was performed.Results:The analysis showed the normal follow-up activity of the palliative care unit that was focused on controlling symptoms, sharing information and providing advice on therapeutic regimens and care. The environment appeared to condition the patients' expressions and the type of patient relationship. Favorable clinical encounter conditions included kindness and gratitude. Unfavorable conditions were deterioration caused by approaching death, unrealistic family objectives and limited resources.Conclusion:Home visits from basic palliative care teams play an important role in patient and family well-being. The visits seem to focus on controlling symptoms and are conditioned by available resources.